Influence of Energy Sector Corporations on the Corporate Control Functions of Cities - RaÅºniak, Piotr; Dorocki, SÅ‚awomir; RachwaÅ‚, Tomasz; Winiarczyk-RaÅºniak, Anna (International Journal of Energy Economics and Policy, 2021)
The energy sector is one of the most important industrial sectors, especially in the era of depleting sources of mineral fuels, climate-related threats resulting from negative effects of energy production from fossil fuels on the natural environment, and the associated need to develop energy sources based on renewable sources. Hence, the financial performance of firms in the energy sector, especially the largest firms, is an important research issue. The purpose of this paper is to determine the financial position of the largest firms in the energy sector listed by Forbes Global 2000 and their impact on the command and control (C&C) functions of cities. In this paper, we present a index of potential for selected cities based on revenue from sales, net profits, assets, and market value for selected sectors of the economy (CCI). Research has shown that the energy sector is one of the leading sectors in the world economy, both in terms of corporate financial performance and as a whole. However, the energy sector is a dominant sector in relatively few cities around the world (Beijing, Moscow, Houston, the Hague). At the same time, the energy sector is considered not very stable relative to other sectors of the economy. Given the increasing importance of the largest firms in this sector in shaping the command and control function of cities, it would be reasonable to combine the forecasting of their financial performance with a focus on its impact on the command and control function of cities in order to evaluate patterns associated with this function for leading cities in the world. Keywords: energy sector, command and control function of cities, financials, resources JEL Classifications: F3, G3, R1 DOI: https://doi.org/10.32479/ijeep.10687